PEMBUATAN ELEKTRODA DAN PERANCANGAN SISTEM CAPACITIVE DEIONIZATION UNTUK MENGURANGI KADAR GARAM PADA LARUTAN SODIUM CLORIDA (NaCl) - Himmaty, Ikfina; Endarko, Endarko (BERKALA FISIKA, 2013)
Fabrication of electrode and design of capacitive deionization (CDI) have been successfully carried out. Electrodes have been made using an activated carbon from coconut shell, graphite andepoxy with ratio 82:10:8. Mixture of activated carbon and graphite poured on an epoxy solution, andthen it was added with hardener and epoxy resin (1:1). Electrodes with dimension of 8 × 6 × 0.3 cmhave been made with doctor blade method. Specific capacitance of the electrode measured at 7.8 mF/gwith porosity 13.4%. Desalination is done by passing a solution of NaCl 0.5 M with a flow rate 3.5 ml/min in the CDI system. Salt removal in the capacitive deionization can be measured withconductivity parameter of NaCl solution before and after the desalination process. Calculation ofpercentage reduction in NaCl concentration can be determined by the decrease in conductivity of thesolution after desalination. The results showed that the maximum percentage reduction of salt levels inthe NaCl 0.5 M solution for configurations of monopolar and bipolar were achieved at 10.4% and4.3%, respectively, within 5 minutes of testing time.Keywords: capasitive deionisation (CDI), desalination, activated carbon from coconut shell